Development of internet finance industry with the core of e-commerce platform services optimised by the edge computing of the internet of things based on artificial intelligence. (16th March 2022) - Yu, Baojun; Zhao, Anni
This article mainly discusses how to use internet edge computing to optimise IoT logistics services. This article conducted face-to-face interviews with 178 online shoppers and invited them to fill out a structured questionnaire. Finally, the data was analysed using Pearson correlation and multiple regression models. The results show that service recovery, delivery service and customer service are positive factors affecting customer satisfaction. The internet of things optimised based on artificial intelligence edge computing is of great significance to the service optimisation of e-commerce platforms.